Pemanfaatan Media Komunikasi Whatsapp Untuk Mengoptimalisasi Kinerja Jurnalis Ditengah Pandemi Covid-19. - Asta Jaya, I Ketut Manik (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2021)
This study aims to examine more deeply the benefits of Whatsapp communication media to optimize the performance of journalists in the midst of the covid 19 pandemic. Especially now that the whole world including Indonesia is still in the midst of the covid-19 pandemic, thus requiring all activities to be limited while still implementing health protocols. In the midst of this condition, technological advances with various features are a solution to keep carrying out various activities, especially the profession as a journalist. This study uses a quantitative approach because it uses research strategies such as survey activities that require statistical data. The results of this study indicate the high use of the Whatsapp application by respondents who are all journalists. In fact, one of the results of the questionnaire distributed through Google Forms shows that 100 percent of respondents choose the use of the Whatsapp application compared to applications such as Facebook, Twitter, Google Meet and other applications. These results show that the Whatsapp application supports the performance of journalists, especially in the midst of the covid 19 pandemic. In addition, the dominant respondents also choose the Whatsapp application to disseminate news links, compared to social media such as Facebook, Twitter and others. This result also causes many features in the Whatsapp application that support performance as a journalist. There are several features in the Whatsapp application: 1. Can send text messages, 2. Receive and send photos from live cameras or albums, 3. Send videos, 4. Exchange documents both in the form of files and others and various other features